2014
DOI: 10.1002/cphc.201402591
|View full text |Cite
|
Sign up to set email alerts
|

Molecular‐Recognition‐Assisted pKa Shifts and Metal‐Ion‐Induced Fluorescence Regeneration in p‐Sulfonatocalix[6]arene‐Encapsulated Acridine

Abstract: The host-guest interactions of cationic (AcH(+) ) and neutral (Ac) forms of the dye acridine with the macrocyclic host p-sulfonatocalix[6]arene (SCX6) were investigated by using ground-state absorption, steady-state and time-resolved fluorescence, and NMR measurements. The cationic form undergoes significant complexation with SCX6 (Keq =2.5×10(4)  M(-1) ), causing a sharp decrease in the fluorescence intensity and severe quenching in the excited-state lifetime of the dye. The strong binding of the AcH(+) form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In a separate investigation, Mohanty et al investigated the effect of pH on the binding behavior of 192 (Figure ) with acridine. Fluorescence spectroscopy analysis revealed that calix 192 bound acridine most strongly in acidic media, where the protonated N atom (p K a of acridinium ion = 5.58) forms attractive Coulombic interactions with the host.…”
Section: Higher Calixarenesmentioning
confidence: 99%
“…In a separate investigation, Mohanty et al investigated the effect of pH on the binding behavior of 192 (Figure ) with acridine. Fluorescence spectroscopy analysis revealed that calix 192 bound acridine most strongly in acidic media, where the protonated N atom (p K a of acridinium ion = 5.58) forms attractive Coulombic interactions with the host.…”
Section: Higher Calixarenesmentioning
confidence: 99%
“…SCXs are extensively used in enzymatic assays, metal-ion sensors/extractants, drug binding, medicine etc. 13,14 The portals of SCXs can bind small guest molecules through electrostatic and more specific interactions like H-bonding, p-stacking, etc. [14][15][16] and in the present context, the cavity can encapsulate the amino acid residue through hydrophobic interaction and helps in the stabilization the a-helices of the protein, which in turn prevents its transformation to the b-sheets.…”
mentioning
confidence: 99%
“…13,14 The portals of SCXs can bind small guest molecules through electrostatic and more specific interactions like H-bonding, p-stacking, etc. [14][15][16] and in the present context, the cavity can encapsulate the amino acid residue through hydrophobic interaction and helps in the stabilization the a-helices of the protein, which in turn prevents its transformation to the b-sheets. 17 On the other hand, disintegration/dissolution of mature fibrils or plaques into smaller particles is another competent remedial approach to target fibril deposits/plaques.…”
mentioning
confidence: 99%
“…This has led to related applications in the investigations of micro-heterogeneous and confined media such as micelles [35], cyclodextrins and calixarenes [36]. For example, Mohanty and co-workers revealed that the protonated form of Ac exhibits a stronger interaction with p-sulfonatocalix [6]arene than does the neutral form [37], which leads to a large upward pKa shift (∼2 units) for the dye.…”
Section: Introductionmentioning
confidence: 99%